Cancer-Therapy-Related Cardiac Dysfunction: Latest Advances in Prevention and Treatment - Carla Contaldi; Carmine D’Aniello; Domenico Panico; Andrea Zito; Paolo Calabrò; Emilio Di Lorenzo; Paolo Golino; Vincenzo Montesarchio (Life)
The increasing efficacy of cancer therapies has significantly improved survival rates, but it has also highlighted the prevalence of cancer-therapy-related cardiac dysfunction (CTRCD). This review provides a comprehensive overview of the identification, monitoring, and management of CTRCD, a condition resulting from several treatments, such as anthracyclines, HER2-targeted therapies, target therapies, and radiotherapy. The paper includes a discussion of the mechanisms of CTRCD associated with various cancer treatments. Early detection through serum biomarkers and advanced imaging techniques is crucial for effective monitoring and risk stratification. Preventive strategies include pharmacological interventions such as ACE inhibitors/angiotensin receptor blockers, beta-blockers, and statins. Additionally, novel agents like sacubitril/valsartan, sodium-glucose co-transporter type 2 inhibitors, and vericiguat show promise in managing left ventricular dysfunction. Lifestyle modifications, including structured exercise programs and optimized nutritional strategies, further contribute to cardioprotection. The latest treatments for both asymptomatic and symptomatic CTRCD across its various stages are also discussed. Emerging technologies, including genomics, artificial intelligence, novel biomarkers, and gene therapy, are paving the way for personalized approaches to CTRCD prevention and treatment. These advancements hold great promise for improving long-term outcomes in cancer patients by minimizing cardiovascular complications.